Effect of Salinity and Nitrogen Form in Irrigation Water on Growth, Antioxidants and Fatty Acids Profiles in Halophytes Salsola australis, Suaeda maritima, and Enchylaena tomentosa for a Perspective of Biosaline Agriculture - Cassandre Certain; Luc Della Patrona; Peggy Gunkel-Grillon; Audrey Léopold; Philippe Soudant; Fabienne Le Grand (Agronomy, 2021)
Cultivation of salt-tolerant crops help to face to irreversible global salinization of freshwater and soils. In New-Caledonia, three halophytes are candidates for saline crops, Salsola australis R.Br., Suaeda maritima (L.) Dumort and Enchylaena tomentosa R.Br. Their success and quality depend yet on availabilities of salinity and essential nutrients in agrosystems. So, we investigated effects of three salinities, i.e., control moderate and high, and five nitrogen ratios, i.e., 100:0, 75:25, 50:50, 25:75 or 0:100 NO3−-N:NH4+-N ratio on their growth and functional value for fatty acids and antioxidants. Results show that the leaf fatty acid and antioxidant profiles of species, emphasize their good potential to become functional crop products, based on comparison with other functional plants, dietetic recommendation, or functional indices. However, their total phenolic compounds (TPC) content can be influenced by N-ratio (Suaeda maritima and Enchylaena tomentosa) and their antioxidant activity index (AAI) can be influenced by salinity (Suaeda maritima), N-ratio (Salsola australis) or both (Enchylaenatomentosa). Their quantitative and/or qualitative fatty acid profiles can also be influenced by salinity (Enchylaena tomentosa), N-ratio (Suaeda maritima), or both (Salsola australis). Regarding these variations, involving salt tolerance and nitrogen nutrition mechanisms, we recommend suitable treatments to maintain or optimize the growth and the functional quality of leaves in the three species.